Locating Facilities for After-Sales Services in a Two-Level Nested Hierarchy: - - Effects of service levels on location patterns and costs - Jat, Mohsin Nasir (2007)
Different service levels in an after-sales service environment results in different patterns of facility location in an area. The criticality of service need by customers dictate the level of services that company provides. If the service needs to be provided in a short span of time, the resulting pattern of facility placement is a decentralized one. Decentralized storage and service centres result in more responsiveness to customers but they also increase the costs significantly. The following thesis is aimed to analyse these effects and attempts to answer the issue of how to locate facilities to get optimum results. For this purpose different costs and their behaviours are analysed in accordance to different settings.